1995
DOI: 10.1021/ac00101a026
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman Observation of Surface Carbonyl Groups on Carbon Electrodes Following Dinitrophenylhydrazine Derivatization

Abstract: Dinitrophenylhydrazine (DNPH) was used to form hydrazone derivatives of carbonyl groups on glassy carbon (GC) and pyrolytic graphite surfaces. The DNPH adducts of (10)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 2 publications
3
50
0
Order By: Relevance
“…The main reason is that the lowest potential applied during the CV was 0 V, thus avoiding the reduction of NO 2 into NHOH group as demonstrated before. Only a little, bad-defined reversible system was observed around 0.27 V on both grafted and unmodified electrodes and was assumed to belong to the quinone redox system often observed on GC after polarization [40][41][42]. The same behavior was obtained when the electrolysis at 0.3 V was performed in acetonitrile containing 2.5 mM NBD.…”
Section: Influence Of Grafting Potentialsupporting
confidence: 55%
“…The main reason is that the lowest potential applied during the CV was 0 V, thus avoiding the reduction of NO 2 into NHOH group as demonstrated before. Only a little, bad-defined reversible system was observed around 0.27 V on both grafted and unmodified electrodes and was assumed to belong to the quinone redox system often observed on GC after polarization [40][41][42]. The same behavior was obtained when the electrolysis at 0.3 V was performed in acetonitrile containing 2.5 mM NBD.…”
Section: Influence Of Grafting Potentialsupporting
confidence: 55%
“…Figure 4 shows the Raman spectra of (a) DNPH-oxiBSA and (b) BSA, and (c) the difference between (a) and (b), and (d) the Raman spectrum obtained for the protein-free DNPH solution. Evidently, DNPH and BSA conjugation, produces a marked change in the DNPH Raman spectra, mainly the red-shift of both the 1355 cm −1 peak (the dinitrophenyl-N bond stretch [36]), and the 848 cm −1 peak (ring breathing mode [37]). The major protein Raman features including the 1003 cm −1 phenylalanine peak and 1430 cm −1 methylene scissoring peak remains largely unchanged before and after DNPH conjugation.…”
Section: Resultsmentioning
confidence: 99%
“…2. ), which has previously been shown by XPS to dramatically increase the number of carboxylic acid groups at the CNT surface [32,33]. It has also been recently demonstrated that a Ni electrode (oxidised to NiO(OH) at pH 10) is effective for NH 3 oxidation [15].…”
Section: Response To Ammoniamentioning
confidence: 87%